How HR professionalism and Employee voice drive Organizational commitment and engagement - Van, Vu Hong; Pham, Duong Ngoc; Tram, Nguyen Thi Minh; Trang, Le Thi Thanh (Edelweiss Applied Science and Technology, 2025)
This study examines the impact of HR professionalism and employee voice on organizational commitment and work engagement within sustainability-focused enterprises. It highlights how perceptions of HR practices influence organizational outcomes, contributing to the understanding of HR strategies for sustainability. Design/methodology/approach – A quantitative study was conducted with 1,058 employees from 24 sustainability-driven enterprises, employing Structural Equation Modeling (SEM) to analyze the relationships among HR professionalism, employee voice, HR attributions, organizational commitment, and work engagement. The theoretical framework integrates the Resource-Based View, Attribution Theory, and Social Exchange Theory. Findings – HR professionalism positively influences employee voice, which, in turn, enhances organizational commitment and work engagement. HR attributions play a key mediating role, highlighting how employees’ perceptions of HR practices shape their attitudes and behaviors. The results underscore the strategic importance of HR in fostering positive employee outcomes. Practical implications – Organizations seeking to enhance commitment and engagement, particularly in sustainability contexts, should prioritize HR professionalism and actively promote employee voice. HR managers can drive performance by fostering transparency, trust, and open communication, aligning employee behaviors with organizational objectives. Originality/value – This study bridges HR management and sustainability, offering new insights into how HR professionalism and employee voice influence organizational outcomes. It provides practical guidance for businesses addressing sustainability challenges.